Cultural Identity of Blacks and Whites In Toni Morrisonâ€™s Song of Solomon: A Perspective of Postmodernism - Supriyatno, Supriyatno; Suyono, Suyono; Khasanuddin, Khasanuddin (Jurnal Budaya, 2020)
AbstractGrasping the cultural identity in a society is the characteristic and signifier to the existence and dimension of society in their life. Life of community in the broadest sense exists in paradigm of reflection and representation in the plots of norm, ideology, tradition and aesthetic involved in and it should not be the dichotomy in space and time in transferring the meaning of life. It is the forms of integrity, responsibility in orders of values, hope, ideals and future. The article represents the life of human being in following, encouraging, accompanying, even fighting for how to reach the cultural identity in terms of rational and historical times. Colored with the problems of social stratification, race, and gender, this novel tries to convey the forms of paradoxical analyses and sharp elaboration in the structure of oxymoron implying on the studies of culture in a society as to find out the self-identity. The analyses of the research are in the approach of post-modernism discussed as the reaction to the established modern era and its colors, meanwhile the data are analyzed in terms of qualitative method with the techniques of interpretative qualitative in the steps of comprehensive data reading, meaning interpretation and critical analysis.Keywords: Cultural Identity, Song of Solomon, Post-ModernÂ AbstrakMemegang identitas budaya dalam masyarakat merupakan karakteristik dan penanda eksistensi dan dimensi kehidupan masyarakat. Kehidupan masyarakat dalam makna luas ada dalam paradigma refleksi dan representasi dalam alur norma, ideologi, tradisi dan estetika di dalamnya dan seharusnya tidak ada dikotomi ruang dan waktu dalam mentransfer makna kehidupan. Hidup merupakan bentuk integritas dan tanggung jawab dalam tatanan nilai, harapan, cita-cita dan masa depan. Artikel ini merepresentasikan kehidupan manusia dalam mengikuti, mendorong, mengiringi, bahkan berjuang meraih identitas budaya dalam terminologi rasionalitas dan kesejarahan. Diwarnai masalah-masalah stratifikasi sosial, ras, dan jenis kelamin, novel ini mencoba mengungkapkan bentuk-bentuk paradoks dan uraian tajam dalam struktur oxymoron berimplikasi pada kajian budaya dalam masyarakat untuk menemukan jati dirinya. Analisis penelitian ini menggunakan pendekatan post-modernisme mendiskusikan reaksi terhadap kemapanan era modern dan segala bentuk warnanya, sedangkan data dianalisis menggunakan metode kualitatif dengan teknik kualitatif interpretatif melalui langkah-langkah membaca data secara komprehensif, interpretasi makna dan analisis kritis.Kata Kunci: Identitas Budaya, Song of Solomon, Post-Modernisme.